Evaluation of NAFTA - Weintraub, Sidney (1997)
Looks at some of the arguments made against NAFTA at the time of its creation and subjects them to a reality check three years later. Focuses on arguments made in the United States with respect of free trade with Mexico. Sets forth criteria that should not be used to evaluate NAFTA, those that should be used employed and assesses the results of the agreement based on the latter.